The BACE gene: genomic structure and candidate gene study in late-onset Alzheimer's disease. - Murphy, T; Yip, A; Brayne, C; Easton, D; Evans, J; Xuereb, J; Cairns, N; Esiri, M; Rubinsztein, D (2001)
Alzheimer's disease (AD) pathology is characterized by beta-amyloid plaques and neurofibrillary tangles. Studies of autosomal dominant early-onset AD mutations suggest that beta-amyloid overproduction is sufficient to cause AD. Recently, the BACE gene, which encodes beta-secretase, the rate limiting enzyme in beta-amyloid formation, has been identified. Since this gene is a strong candidate gene for late-onset AD because of its function, we have characterized its genomic organization and identified two polymorphisms. Neither of these polymorphisms were associated with AD risk in genetic association studies comparing autopsy-confirmed late-onset AD cases and age-matched non-demented controls. Thus, we find no evidence that this locus influences risk for late-onset AD.